Inclusive Leadership And Employee Productivity: The Strategic Role Of Board Gender Diversity And Female Executives - Darojat, Abdul Rouf; Ayyub, Noor Muhammad; Cahyono, Ari (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study explores how gender-inclusive leadership structures influence organizational performance, particularly employee productivity. It examines three dimensions: board gender diversity, the presence of female executives (e.g., CEO or board chair), and their interaction. Grounded in Resource-Based and Social Identity Theories, the research hypothesizes that (H1) board gender diversity positively affects productivity; (H2) female top leadership enhances productivity; and (H3) their interaction amplifies these effects.Using quantitative methods and data from publicly listed companies across various industries, the study controls for factors such as firm size, industry, and market conditions. The analysis reveals strong direct effects of board diversity and female leadership on productivity, while age, as a mediating variable, shows a negligible and slightly negative influence. These findings underscore the strategic value of inclusive leadership in fostering workforce performance and suggest that organizations should prioritize gender diversity and female representation in leadership to improve productivity outcomes.